Shifting IP Battlegrounds in the U.S.–China Trade War - Lee, Jyh-An (The Columbia Journal of Law & the Arts, 2020)
Intellectual property (“IP”) represents one of the main controversies of U.S.– China trade relations in the past three decades and remains one of the core issues behind the two countries’ recent trade frictions. This Article provides an overview of the current IP debates between the two largest economies in the world. It illustrates the transformation of the Chinese government’s role from inactive IP law enforcer to active facilitator of access to and acquisition of foreign technologies. This study further explains how China’s approach to learning western technologies has transformed from low-end imitation to gaining a controlling stake in foreign companies via joint ventures or outbound investments. More importantly, this Article discusses the legal and policy implications of the IP issues in this trade war. I argue that the recent IP trade war represents the struggle for global technological leadership as well as a new institutional competition in the post-Cold War era. Moreover, China’s “economic aggression,” as the United States understands it, has caused a number of unsolved issues for the international IP regime, which include the justification of China’s controversial IP policies for the purpose of industrial catch-up as well as the evidentiary and legal bases for holding China liable for its economic aggression in relation to IP.